Emerging roles of endoplasmic reticulum stress in the cellular plasticity of cancer cells - Wang, Hao; Mi, Kun (Frontiers in Oncology, 2023)
Cellular plasticity is a well-recognized dynamic characteristic of tumor cells, which endows tumors with heterogeneity and therapy resistance, and alters their invasion-metastasis progression, stemness, and sensitivity to drugs, thus representing a major challenge to cancer therapy. It is increasingly accepted that ER stress is a hallmark of cancer, and aberrant activation of ER stress sensors and their downstream signaling pathways participate in the regulation of tumor progression and cellular response to multiple challenges. Moreover, accumulating evidence revealed the involvement of ER stress in cancer cell plasticity regulation, including epithelial-mesenchymal plasticity (EMP), drug resistance phenotype, cancer stem cell (CSC) phenotype, and vasculogenic mimicry (VM) phenotype plasticity. ER stress alters the phenotypic characteristics of tumor cells, disrupts tissue homeostasis, induces epithelial/mesenchymal transition, the gain or loss of stemness, reversible drug resistance, the remodeling of angiogenic function, and renders tumor cells to survive changing microenvironments and resist therapy. In this review, we discuss the emerging links between ER stress and cancer cell plasticity implicated in tumor progression and chemoresistance, which might provide an update on therapeutic strategies to target ER stress and cancer cell plasticity in anticancer treatments.